2019
DOI: 10.1017/s0954579419001135
|View full text |Cite
|
Sign up to set email alerts
|

Early life predictors of attention deficit/hyperactivity disorder symptomatology profiles from early through middle childhood

Abstract: This study used repeated measures data to identify developmental profiles of elevated risk for ADHD (i.e., six or more inattentive and/or hyperactive-impulsive symptoms), with an interest in the age at which ADHD risk first emerged. Risk factors that were measured across the first 3 years of life were used to predict profile membership. Participants included 1,173 children who were drawn from the Family Life Project, an ongoing longitudinal study of children's development in low-income, nonmetropolitan communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Additionally, and consistent with our hypothesis [ 22 , 23 ], we found that a maternal authoritarian parenting style is associated with children’s later inattentive/hyperactive symptoms. Some previous studies suggest that harsh and/or intrusive parenting may be related to the disrupted development of children’s attentional control [ 9 , 22 , 23 ]. It has been reported that maternal intrusiveness at 6 months old or maternal overstimulating behaviour at 3.5 years old, as measured by questionnaires, are associated with teachers reporting more ADHD symptoms at 11 years old.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, and consistent with our hypothesis [ 22 , 23 ], we found that a maternal authoritarian parenting style is associated with children’s later inattentive/hyperactive symptoms. Some previous studies suggest that harsh and/or intrusive parenting may be related to the disrupted development of children’s attentional control [ 9 , 22 , 23 ]. It has been reported that maternal intrusiveness at 6 months old or maternal overstimulating behaviour at 3.5 years old, as measured by questionnaires, are associated with teachers reporting more ADHD symptoms at 11 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, previous research on early parenting and later symptoms of inattention/hyperactivity have also reported contradictory findings [ 9 , 22 , 23 , 37 40 ]. These studies suggest that poorer parenting in early childhood may serve as a risk factor that moderates and exacerbates a child’s predisposition to present symptoms of inattention and hyperactivity.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations